2009
DOI: 10.1103/physrevb.79.121403
|View full text |Cite
|
Sign up to set email alerts
|

Superstructure in the termination of CoO(111) surfaces: Low-energy electron diffraction and scanning tunneling microscopy

Abstract: The surface structures of CoO͑111͒ films epitaxially grown on Ir͑100͒ − ͑1 ϫ 1͒ are investigated by means of quantitative low-energy electron diffraction and scanning tunneling microscopy. A ͑ ͱ 3 ϫ ͱ 3͒R30°superstruc-ture is revealed for the films' ground states. It appears for film thicknesses Ն10 Å both for strained and unstrained films and so most likely applies also to the ͑111͒ surface of a bulk CoO crystal. The superstructure is interpreted as a stress-relieving reaction to the switch from rocksalt-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…Only four of the oxygen ions ͑O high ͒ are located, as expected, i.e., in or near hollow sites formed by the underlying Co ions. The Co-O high bond lengths are with an average of 1.85 Å ͑variational range 1.81-1.87 Å͒ identical to that found for the outermost Co-O bonds in thicker CoO films, 4 where the local oxygen coordination is the same as in the present case. The other five oxygen ions ͑O low ͒, however, are pushed into the surface by almost 1 Å with respect to the other ones.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Only four of the oxygen ions ͑O high ͒ are located, as expected, i.e., in or near hollow sites formed by the underlying Co ions. The Co-O high bond lengths are with an average of 1.85 Å ͑variational range 1.81-1.87 Å͒ identical to that found for the outermost Co-O bonds in thicker CoO films, 4 where the local oxygen coordination is the same as in the present case. The other five oxygen ions ͑O low ͒, however, are pushed into the surface by almost 1 Å with respect to the other ones.…”
Section: Discussionsupporting
confidence: 81%
“…On this background and as the structures of nanosized solids frequently differ from their bulk structures, we have studied ultrathin cobaltoxide films in the recent past whereby the Ir͑100͒-͑1 ϫ 1͒ surface has been used as support. 2 In fact, we have found that the surfaces of CoO films grown in ͑111͒ orientation deviate substantially from the rocksalt structure 3,4 ͓the large lattice misfit between CoO and Ir of about 10% prohibits pseudomorphic growth in ͑100͒ orientation͔.…”
Section: Introductionmentioning
confidence: 98%
“…33,34 Here, various other factors were considered, in particular the presence of oxygen vacancies and surface Co 2+ ions. [38][39][40][41][42][43][44][45][46][47][48] In a unique fashion, these films allow varying the stoichiometry, the surface orientation, the film thickness, and the defect density. 29 The present work aims at the development of new cobaltoxide-based model systems which allow us to study their surface chemistry under well-controlled ultrahigh vacuum (UHV) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt oxides have found interesting applications in many diverse fields of the advanced technologies, 8 and the epitaxial growth of Co oxide thin films has been reported on various metal substrates, such as Ag(100), [9][10][11][12][13] Ir(100), [14][15][16][17][18] and Pd(100). 8 have been described as a function of film thickness: while for thicker films (>10 ML) the oxide overlayers converge to the known bulk phases of CoO and/or Co 3 O 4 , the films in the ultrathin limit of 2D structures depend on the particular metal substrate and the thermodynamic and kinetic parameters of the deposition.…”
Section: Introductionmentioning
confidence: 99%